Value relevance of aggregated vs disaggregated book value and earnings : evidence from Malaysian high-tech firms / Mohd Halim Kadri, Muhd Kamil Ibrahim and Rozainun Abdul Aziz. - Kadri, Mohd Halim; Ibrahim, Muhd Kamil; Abdul Aziz, Rozainun (Universiti Teknologi MARA Cawangan Selangor, 2010)
This study is aimed at investigating the value relevance of aggregated and disaggregated book value and earnings of high-tech firms listed on Bursa Malaysia for the period from 2003-2008. Using the Ohlson (1995) basic and modified equity valuation models, this study investigated whether disaggregated book value and earnings could explain the variation in market value better than aggregated book value and earnings. The results of the basic model show that the explanatory powers of both book value and earnings are fluctuating with book value is in a decreasing trend whereas earnings is in an increasing trend. The results of the modified models show that disaggregated book value and earnings could explain the variation in market value better than aggregated book value and earnings.